Some preservation properties of MKZ-Stancu type operators - Erençin, Ayşegül; Başcanbaz-Tunca, Gülen; Taşdelen, Fatma (Sarajevo Journal of Mathematics, 2024)
In this work, we construct Stancu type modification of the generalization of Meyer-König and Zeller operators (MKZ) defined in [12]. We show that the Lipschitz constant of a Lipschitz continuous function and the properties of the function of modulus of continuity can be retained by these operators.